INSTITUTIONAL STRATEGY VS. REAL-TIME RESPONSE: DISCOURSE PATTERNS IN COVID-19 PRESS CONFERENCES - Tamta Goradze,; Zeinab Gvarishvilii, (International Journal of Innovative Technologies in Social Science, 2025)
The COVID-19 pandemic triggered a global crisis that had far-reaching consequences beyond public health. It disrupted every aspect of human life and global systems. Responsible persons on crisis management had to play a vital role in making decisions, allocating resources, enforcing policies, along with effective communication, which comprised disseminating accurate information, countering misinformation, and encouraging adherence to safety protocols. Despite the prevalence of online communication and social media, global crises have demonstrated that news conferences are still the preferred technique of information dissemination. Press conferences are not chosen at random for political speeches, rather, they are valued for their procedural and general characteristics, particularly in situations of crisis, due to their interactive, dynamic, and collaborative nature. A press conference is a rhetorical response to an urgent situation, with three basic speech acts: introduction, defense of a position and addressing skepticism. These communication acts are carried out through a various strategic maneuver. The study highlights the significance of press conferences in crisis situations and their role as a strategic communication tool. While press conferences undoubtedly serve institutional needs, the debate remains as to whether they represent intentional strategic communication or emergent responses based on situational factors. Strategic communication can range from intentional to emergent, depending on the context. The research provides a corpus-based comparative and contrastive analysis of a limited number of COVID-19-related discourses from press conferences held by authorities in the USA. Thus, the study focuses on: i. determining the frequency and distribution of pre-selected markers based on a generic analysis of COVID-19-related discourse; ii. examining the pragmatic value of the markers and their intended impact on the audience; iii. comparing and contrasting the frequency and distribution of discourse markers in monologue and question-and-answer (Q&A) segments; iv. identifying the type of strategic communication present in COVID-19 press conferences. The study contributes to a greater understanding of the press conference as a strategic communication tool, rather than as a random channel for information distribution. It explores how press conference functions as strategic communication, ranging from intentional to emergent, shaped by institutional responsibilities.